Effect of As and Ga doping on the electronic structure and photoelectric properties of cubic Ca2Ge. (9th December 2020) - Lyu, Lin; Yang, Yinye; Cen, Weifu; Yao, Bing; Ou, Jiankai
Abstract: The electronic structure and optical properties of intrinsic and doped Ca2 Ge have been calculated by using the first-principles calculation method based on density functional theory. The doping content of As were 2.08% and 1.04%, respectively, and the doping concentrations of Ga were same with As. The band gap of intrinsic Ca2 Ge is 0.556 eV, and that decreased to 0.526 eV and 0.548 eV with respect of As doping amount of 2.08% and 1.04%. Meanwhile, the band gap is 0.25 eV when the doping amount of Ga was 1.04%, and the band gap is 0.23 eV for Ga was 2.08%. The band structures results shown that the Fermi levels of As-doped (2.08% and 1.04%) are moved into the bottom of conduction band. The electronic density of sates shown that the electronic configurations at the top valence band and bottom conduction band were changed as As and Ga doped. The dielectric function results shown that the maximum value of 52.7 and 97.53 were respectively obtained at 0 eV for the 2.08% Ga-doped and the 1.04% As-doped. Moreover, the phenomenon of strong metallic reflection has been found in the energy range of 6.0 ∼ 8.5 eV, and the metal reflection characteristics of intrinsic Ca2 Ge was greater than the doped Ca2 Ge. Analyzing the energy-loss function, it indicating that the energy region of appearing energy loss can be altered by doping As and Ga or changing their doped concentration.